ANALISIS PERENCANAAN SUMBER DAYA MANUSIA DI UNIVERSITAS NUSA CENDANA KUPANG - Leony M Ndoen; Yoseba Pulinggomang; Lukas Hattu; Thomas Isliko (Universitas Nusa Cendana, 2023)
The purpose of the research is to ensure the availability of human resources in the future at the University of Nusa Cendana. The research sample is the Faculty of Social Sciences (FISIP) and the Faculty of Teaching and Education Science (FKIP). The method in data analysis is the forecasting technique. The results showed that the qualifications of FKIP and FISIP lecturers matched the target of the Ministry of Education and Culture, which is the percentage of lecturers who have work experience or are certified educators. Indicators of the adequacy of the number of functional positions; professors, head lectors, and lectors assigned as the lecturer set by BAN-PT are still below the standard. Lecturer-Student Ratio (RDM) is beyond the ideal conditions. The lecturer entering their retirement in 2022 are high, thus the demand for lectures is high. The limitations of this study were the unavailable completed documentation and the limited scope in two faculties only. Keywords: Human Resource Planning; Forecasting; Lecturer-Student Ratio